Digitally aligned ZnO nanowire array based synaptic transistors with intrinsically controlled plasticity for short-term computation and long-term memory. Issue 45 (16th November 2021) - Zhang, Shuo; Yang, Lu; Jiang, Chengpeng; Sun, Lin; Guo, Kexin; Han, Hong; Xu, Wentao
Abstract : S- and L-ZnO NW synaptic transistors prepared from arrays of ZnO NWs of different diameters (100 nm and 500 nm) enable the development of neuromorphic computers that use the same material to achieve both short-term computation and long-term memory. Abstract : Digitally aligned long continuous ZnO NWs with distinct widths and microstructures are prepared and used for tuning the plasticity of synaptic transistors (STs) for the first time. Intrinsically controlled synaptic plasticity, i.e. short-term plasticity (STP) and long-term plasticity (LTP), was achieved using the same source material and post-fabrication condition for the first time, which is essential for simple and low-cost fabrication. Moreover, these versatile properties of ZnO STs enable the integration of STP and LTP as realized by multiplexed neurotransmission of different neurotransmitters: dopamine and acetylcholine, which promote learning and memory in organisms, so the device may utilize these processes in neuroelectronic devices. Devices with well-controlled synaptic plasticity can simulate the "learning–forgetting–erase" and "instant display" processes. ZnO NWs may enable the development of neuromorphic computers that can use the same material to achieve both short-term computation and long-term memory.